Developing intercultural competence in elementary physical education: an online international collaboration between the U.S. and Japan. Issue 2 (4th May 2022) - Tsuda, Emi; Olsen, Edward B.; Sato, Masanobu; Wyant, James D.; Watanabe, Rio
ABSTRACT: This study aimed to explore in-service and pre-service teachers' experiences of conducting an online international collaboration unit, called CULTURE (the Culture Unit of Learning to Understand, Respect, and Empathize) in elementary school physical education in the U.S. and Japan. The study used a narrative research design using semi-structured interviews. The participants were 10 in-service and pre-service teachers from the two countries. A constant comparative method was used to interpret the data. Five emerged themes were: (a) Promoting cultural awareness and appreciation, (b) developing communication skills, (c) producing positive experiences for all, (d) project facilitators and barriers, and (e) applying to future professions. The CULTURE could be one of the approaches to facilitate the development of intercultural competence over time.